Analysis Customers' Interest to IB Faedah Savings - Mohamad Toha; Qurrotu Aini (Majapahit Journal of Islamic Finance and Management, 2021)
Marketing is to attract customers to use BRI Syariah products. In this case, the bank wants its product to be easy to sell and expansive, which is in great demand by customers and prospective customers. The study aims to determine customer’s interest in iB Faedah savings at BRI Syariah KCP Mojosari - Mojokerto. To answer the questions above, this research was designed with a qualitative descriptive approach using a case study approach. Based on the analysis of the data, it can be concluded that 1) Attention, that customers know about the iB Faedah savings product from their own initiative to come to the office and customers know about Faedah savings directly from BRI Syariah. 2) Interest, The reason customers use Faedah savings is because it adjusts to the background of individual status and the good service from BRI Syariah during the procedure. Customers feel well served and receive a clear explanation from BRI Syariah regarding the details of the iB Faedah savings product. 3) Desire, customer interest related to the cost of Faedah saving is said to depend on each person’s perspective and ability. Customers choose products with lower costs and can be used as a means of saving money for their internal needs. 4) Action (Using), that is the reason the customer has the desire to use the iB Faedah savings to meet the business needs. 5) Halal Lifestyle Awareness, customers have a purpose other than to meet financial needs but also to change perspectives in choosing the products used.